Hero's Journey of Aishan in Martin Lings Muhammad : his life based on the earliest sources - Agfitia Saraswati Ustifah (Fak. Adab dan Ilmu Budaya Universitas Islam Negeri Sunan Kalijaga, 2022)
wt,1/ida,c.1